In vitro interaction of Amanita muscaria and Phytophthora cinnamomi: possible biocontrol effect - Rodrigues, Paula (2005)
Ink disease, caused by the Oomycetes Phytophthora cinnamomi Rands. and Phytophthora cambivora (Petri) Buism., is a major soilborne problem in European chestnut (Castanea sativa) stands all over South Europe. Chemical treatments are not effective and comprise serious environmental and economic costs, so biological control is under study as a possible solution for this problem. Ectomycorrhizal (ECM) fungi are generally considered as potential biocontrol agents, for several of them have shown a positive effect on growth and survival of infected plants. The mechanisms underlying these effects are, however, still unknown. It is possible that they result from a chemical antagonism or a physical barrier of the ECM fungus over the pathogen, but other hypotheses involve active responses by the plant. Amanita muscaria is an important ECM fungus of C. sativa in the Northeast of Portugal. The present study intended to investigate a possible antibiosis effect of A. muscaria (Am) over P. cinnamomi (Pc). For this purpose, we used isolates of Am and Pc collected from a local chestnut orchard. The interaction between the organisms was tested by the dual culture technique on Petri dish, using mycelial inoculum, in two different culture media: MMN and PDA. The following dual cultures were tested: Am + Am, Pc + Pc, Am + Pc (inoculated simultaneously) and Am7→Pc (Pc inoculated 7 days after the inoculation of Am). Interaction was analysed daily for a period of seven days (given the rapid growth of Pc), and was based on radial growth and morphological features of both organisms. The growth of P. cinnamomi was heavily constrained by the presence of A. muscaria (in both Am + Pc and Am7→Pc dual cultures), and more spores were formed, when compared with Pc + Pc cultures. The results suggest a heavy antagonistic effect of the ECM fungus over the pathogen. Other ECM fungi are currently under study for the analysis and comparison of possible different effects over P. cinnamomi.